Use of the Selective Oral Neuraminidase Inhibitor Oseltamivir to Prevent Influenza - Hayden, Frederick G; Atmar, Robert L; Schilling, Margo; Johnson, Casey; Poretz, Donald; Paar, David; Huson, Les; Ward, Penelope; Mills, Roger G (The New England journal of medicine, 1999)
Yearly immunization with inactivated vaccines is the main strategy for the prevention of influenza. 1 When substantial antigenic drift occurs after the formulation of a vaccine — as happened, for instance, during the 1997–1998 season, when the A/Sydney/5/97 variant of the H3N2 subtype circulated — large outbreaks may occur, particularly among institutionalized patients at high risk for infection. 2 Influenza B virus may also cause such outbreaks. 3 , 4 The recent cluster of human cases of H5N1-subtype influenza in Hong Kong is another reminder of the continuing threat of pandemic influenza. 5 – 7 In the event of the rapid spread of a new influenzavirus, . . .